Psychosocial, clinical and demographic features related to worry in patients with melanoma. Issue 5 (October 2016) - Rogers, Zoe; Elliott, Faye; Kasparian, Nadine A.; Bishop, D. Timothy; Barrett, Jennifer H.; Newton-Bishop, Julia
Abstract : The aim of this study was to investigate clinical, demographic and psychosocial predictors of melanoma-related worry. A questionnaire-based study in a population-ascertained cohort of individuals diagnosed with melanoma in the previous 3–6 months was carried out to identify factors associated with worry about melanoma shortly after diagnosis. A total of 520 patients felt worried about their future with respect to melanoma and 1568 patients felt confident about their future with respect to melanoma. Worry was less likely in men with partners than women with partners [adjusted odds ratio (OR)=0.51, 95% confidence interval (CI) (0.39–0.67)], and increasing age was protective against worry [adjusted OR=0.96 per year, 95% CI (0.95–0.97)]. Worry was more likely for patients with stage III/IV melanoma [adjusted OR=1.90, 95% CI (1.41–2.56) compared with stages IB–IIC], melanoma arising in sun-protected sites (compared with a limb), no occupation (compared with workers), those who reported insufficient emotional support from healthcare providers [adjusted OR=2.20, 95% CI (1.56–3.09) compared with sufficient support], lower knowledge of melanoma [adjusted OR=4.50, 95% CI (2.82–7.18) compared with well informed], perceived financial hardship compared with no financial hardship and over three previous negative life events compared with none/one. Worry about melanoma outcomes after diagnosis is multifactorial in origin.